2019
DOI: 10.1016/j.applthermaleng.2019.113804
|View full text |Cite
|
Sign up to set email alerts
|

A diamond made microchannel heat sink for high-density heat flux dissipation

Abstract: Flow boiling in microchannels is a promising technique for cooling high power-density electronic devices. In this study, a microchannel heat sink using ammonia as working fluid is developed, and its cooling efficiency is experimentally investigated under nonuniform high-density heat flux, which well simulates a practical heat dissipation scenario for microthermal systems. Diamond with high thermal conductivity of 1500 W/mK is selected as the microchannel heat sink material. A total of 37 parallel triangular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Among all known materials, diamond has a record-high thermal conductivity of up to 24 W/cm•K at room temperature, reaching maximum values of up to 285 W/cm•K at temperatures near 63 K [1]. This makes diamond the material of choice for thermal management applications [2][3][4][5][6]. Solving thermal management problems is especially important for modern electronic devices, operating in extreme regimes, which makes diamond a highly used "cutting-edge" material in electronics [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among all known materials, diamond has a record-high thermal conductivity of up to 24 W/cm•K at room temperature, reaching maximum values of up to 285 W/cm•K at temperatures near 63 K [1]. This makes diamond the material of choice for thermal management applications [2][3][4][5][6]. Solving thermal management problems is especially important for modern electronic devices, operating in extreme regimes, which makes diamond a highly used "cutting-edge" material in electronics [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, during the growth process of PCD thin films, defects such as asymmetric thickness, random crystal orientation, and uneven crystal grains frequently occur [63]. These defects lead to a rough surface, which limits the industrial applications of PCD films [69]. Bhat et al [70] reported that the roughness of CVD diamond film on the surface of coated tools greatly impacts the cutting efficiency, machining accuracy, and final surface quality.…”
Section: Pcdmentioning
confidence: 99%
“…The results showed that the heat flux has a significant effect on the heat transfer coefficient, which indicated that nucleate boiling is the dominant mechanism of heat transfer, but this dominant effect is suppressed at high vapor quality. Yang et al [19] carried out an experimental study of the saturated flow boiling heat transfer of ammonia using a triangular microchannel heat sink and visualized the flow pattern under different vapor qualities. Huang et al [20,21] investigated the effect of different parameters on the heat transfer coefficient of flow boiling in microchannels using R1233zd(E), R245fa and R236fa.…”
Section: Introductionmentioning
confidence: 99%